PENINGKATAN KETANGGUHAN DAN KELEKATAN ORANGTUA ANAK BERKEBUTUHAN KHUSUS DALAM MENGATASI STRES PENGASUHAN DI MASA PANDEMIK COVID-19 - Naomi Soetikno; Pamela Hendra Heng; Nevy Prinanda Putri; Inke Ayu Pertiwi (Jurnal Bakti Masyarakat Indonesia, 2021)
Children are a gift from God that is coveted by every married couple. The child will be the hope of the next generation that is better than the child's parents. Parents always expect their children to develop well and perfect physically, socially, mentally and cognitively. However, in reality this desire is sometimes not in line with expectations, especially parents who get their children as children with special needs. In the COVID-19 pandemic situation, handling children with special needs can be a challenge for parents. Many parents are unable to cover up their feelings of stress, anxiety, fear, hopelessness, inadequacy, and panic in a pandemic situation. Moreover, parents who work from home during the pandemic must also divide their time to teach children with special needs to learn from home (study from home) so that the challenges they face are increasing as well. Therefore, to cope with parenting stress, parents need to increase resilience and attachment. The provision of psychoeducation in an effort to increase parental resilience and attachment is an approach used and given to parents in special needs schools during the Covid-19 pandemic. By giving pre-test and post-test to measure the understanding of participant (parents and teachers) regarding the parenting stress, attachment, and resilience, the difference was obtained ranging from 0.02-0.54, which indicated that there was an increase in understanding of the participants. ABSTRAK:Anak adalah anugerah dari Tuhan yang didambakan oleh setiap pasangan suami istri. Anak akan menjadi harapan penerus generasi yang lebih baik dari orangtua sang anak. Orangtua selalu mengharapkan anak mereka dapat berkembang dengan baik dan sempurna secara fisik, sosial, mental dan juga kognitif. Namun pada kenyataannya keinginan tersebut terkadang tidak sesuai dengan harapan, khususnya orangtua yang mendapatkan anaknya sebagai anak berkebutuhan khusus. Dalam situasi pandemic COVID-19, penanganan anak-anak berkebutuhan khusus dapat menjadi tantangan bagi orangtua. Banyak orangtua yang tidak dapat menutupi rasa stres, cemas, takut, putus asa, tidak mampu, dan panik dalam situasi pandemik. Terlebih lagi orangtua yang bekerja dari rumah (work from home) selama pandemik juga harus membagi waktu untuk mengajari anak berkebutuhan khusus belajar dari rumah sehingga tantangan yang dihadapi semakin meningkat pula. Untuk mengatasi stress pengasuhan, orangtua perlu meningkatkan ketangguhan dan kelekatan. Pemberian psikoedukasi dalam upaya peningkatan ketangguhan dan kelekatan orangtua merupakan pendekatan yang digunakan dan diberikan kepada para orangtua di sekolah kebutuhan khusus di masa pandemic Covid-19. Dengan pemberian pre-test dan post-test untuk mengukur pemahaman peserta yakni orangtua dan guru, mengenai stress pengasuhan, kelekatan orangtua, serta ketangguhan orangtua, didapatkan selisih berkisar 0.02-0.54, yang menunjukkan bahwa adanya peningkatan pemahaman dari peserta.